Towards New Robust Zn(II) Complexes for the Ring‐Opening Polymerization of Lactide Under Industrially Relevant Conditions. Issue 7 (29th July 2019) - Schäfer, Pascal M.; Dankhoff, Katja; Rothemund, Matthias; Ksiazkiewicz, Agnieszka N.; Pich, Andrij; Schobert, Rainer; Weber, Birgit; Herres‐Pawlis, Sonja
Abstract: The synthesis of bio‐based and biodegradable plastics is a hot topic in research due to growing environmental problems caused by omnipresent plastics. As a result, polylactide, which has been known for years, has seen a tremendous increase in industrial production. Nevertheless, the manufacturing process using the toxic catalyst Sn(Oct)2 is very critical. As an alternative, five zinc acetate complexes have been synthesized with Schiff base‐like ligands that exhibit high activity in the ring‐opening polymerization of non‐purified lactide. The systems bear different side arms in the ligand scaffold. The influence of these substituents has been analyzed. For a detailed description of the catalytic activities, the rate constants k app and k p were determined using in‐situ Raman spectroscopy at a temperature of 150 °C. The polymers produced have molar masses of up to 71 000 g mol −1 and are therefore suitable for a variety of applications. Toxicity measurements carried out for these complexes proved the nontoxicity of the systems. Abstract : Fake plastic lactides : New robust and non‐toxic dizinc complexes for the ring‐opening polymerization of rac ‐lactide under industrial relevant conditions are presented. The kinetic measurements have been performed using in situ Raman‐spectroscopy showing that the systems are a perfect alternative for Sn(Oct)2 .